Penggunaan Media Berbasis Hands-on Activity untuk Meningkatkan Minat Belajar Peserta Didik di MI Manbail Futuh Jenu - Maulidya Lailatul Fa'idah; Rizki Afandi; Ahmad Roghibus Sunan; Misbahul Huda (STIKes Ibnu Sina Ajibarang, 2025)
This study is motivated by the low learning interest of students at Madrasah Ibtidaiyah (MI) Manbail Futuh Jenu due to conventional teaching methods that are less engaging. The purpose of this research is to develop and implement hands-on activity-based learning media and to evaluate its effectiveness in increasing students’ learning interest. The method used is qualitative research with data collection techniques including observation, interviews, and documentation. The results show that hands-on activity-based media significantly improve students’ learning interest, conceptual understanding, and critical thinking skills. Students become more enthusiastic, active, and independent in the learning process. Despite challenges such as limited tools and time, this media positively impacts the teaching and learning process. The implications emphasize the importance of developing interactive and practical learning media, along with the need for facility support and teacher training to optimally implement hands-on activities at MI. Thus, hands-on activity-based media can be an effective strategy to enhance the quality of education at the Madrasah Ibtidaiyah level.